A high reliability survey of discrete Epoch of Reionization foreground sources in the MWA EoR0 field - Carroll, P.; Line, J.; Morales, M.; Barry, N.; Beardsley, A.; Hazelton, B.; Jacobs, D.; Pober, J.; Sullivan, I.; Webster, R.; Bernardi, G.; Bowman, J.; et al. (Oxford University Press, 2016)
Detection of the epoch of reionization HI signal requires a precise understanding of the intervening galaxies and AGN, both for instrumental calibration and foreground removal. We present a catalogue of 7394 extragalactic sources at 182 MHz detected in the RA = 0 field of the Murchison Widefield Array Epoch of Reionization observation programme. Motivated by unprecedented requirements for precision and reliability we develop new methods for source finding and selection. We apply machine learning methods to self-consistently classify the relative reliability of 9490 source candidates. A subset of 7466 are selected based on reliability class and signal-to-noise ratio criteria. These are statistically cross-matched to four other radio surveys using both position and flux density information. We find 7369 sources to have confident matches, including 90 partially resolved sources that split into a total of 192 sub-components. An additional 25 unmatched sources are included as new radio detections. The catalogue sources have a median spectral index of -0.85. Spectral flattening is seen towards lower frequencies with a median of -0.71 predicted at 182 MHz. The astrometric error is 7 arcsec compared to a 2.3 arcmin beam FWHM. The resulting catalogue covers ~1400 deg2 and is complete to approximately 80 mJy within half beam power. This provides the most reliable discrete source sky model available to date in the MWA EoR0 field for precision foreground subtraction.